The Influence of Market Day Activities on Expressive Language Skills in Children Aged 5-6 Years - Istigfarin, Izza Rania; Reza, Muhammad; Fairuzillah, Muhammad Naufal; Setyowati, Sri (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This research examine the influence of market day activities on the development of expressive language skills in children age 5-6 years. The background of this research is based on the limited expressive language ability of children in understanding word meanings and constructing sentence structures. Market day activities are expected to serve as interactive and collaborative learning experiences that can enchance children’s expressive language skills. This research employed a Quasi Experimental Design with a Nonequivalent Pretest-Posttest Control Group Design. The research involved 15 children of TK Siti Aminah as a experimental group and 15 children of TK Baiturrahman as a control group. Pretest results showed there is significant differences between the two groups. However after the market day treatment and through hypothesis testing using the Mann Whitney U Test, a significant difference was found. The experimental group demonstrated a notable improvement in expressive language skills compared to the control group. These findings indicate that market day activities have a positive impact on the expressive language development of children aged 5-6 years.